ANALISIS PERSEPSI KONSUMEN TERHADAP KUALITAS PRODUK KEBAB FETIH TURKI (KULINER SYARIAH GROUP) - Wahyu Firmansyah (Jurnal Dinamika Manajemen, 2016)
The purpose of this research is to explain and analyzes consumer perception on the quality product Kebab Fetih Turki (Syariah Kuliner Group). The research is survey. Data collection is done by using a question given to consumers respondents. The research consumer perception of quality product Kebab Fetih Turki dominan by respondent women as many 68 % with early adolescence was between 15 - 20 years as many as 40 % with high school education as many as 43 % with background as student or studen university as many as 45 % and consumes kebab 3- 4 times per week as many as 41 %. An analysis of consumer perception on the quality product Kebab Fetih Turki in variable feature product with the assessment of very good fit because of kebab constitute the food of the peculiarities of turkish state of highly favored consumers with various a menu of choices with the manner of presentation of quick and can wait. The performance by good judgment. The reliability by good judgment. Durability by good. Conformance by good judgment. Aesthestic by good judgment. Perceived quality by good judgment. From the research can be suggested Kebab Fetih Turki could improve the reliability of a product on the equipment that was used in the stands the sale so it can support a product cleanlinessKebab fetih turkey can use of beef processed with high in quality thus produced the accuracy of the product in accordance with the product offered consumers